2019
DOI: 10.1080/20008198.2019.1611092
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of proactive interference control training on intrusive memories

Abstract: Intrusive re-experiencing is a hallmark symptom of Posttraumatic Stress Disorder (PTSD). According to prominent models of intrusive phenomena, intrusive memories may result from impairments in the efficiency of working memory capacity (WMC), more specifically proactive interference control. Yet, experimental research is scarce. Therefore, the present study aimed to investigate experimentally the role of proactive interference control in intrusive memories. We randomly assigned 57 healthy participants to either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
6
0
3
Order By: Relevance
“…On the one hand, a number of studies have identified WMC as a direct [22,23,47,48] or indirect [25] factor modulating intrusive memories or thought suppression. On the other hand, several studies failed to replicate or extend these findings [26,30,[49][50][51]. Jointly, these findings indicate that the relationship between WMC and intrusive trauma memories may be more subtle than often assumed or may be moderated by factors that are not yet fully established.…”
Section: Attention Task Demands and Working Memory Capacitymentioning
confidence: 86%
See 1 more Smart Citation
“…On the one hand, a number of studies have identified WMC as a direct [22,23,47,48] or indirect [25] factor modulating intrusive memories or thought suppression. On the other hand, several studies failed to replicate or extend these findings [26,30,[49][50][51]. Jointly, these findings indicate that the relationship between WMC and intrusive trauma memories may be more subtle than often assumed or may be moderated by factors that are not yet fully established.…”
Section: Attention Task Demands and Working Memory Capacitymentioning
confidence: 86%
“…A fruitful approach might be to investigate this relationship experimentally by means of WMC trainings. For instance, Bomyea and Amir [47] used two training conditions that required high versus low interference control (see also [49]) and found that participants displayed relatively fewer intrusive thoughts in the laboratory following the high interference control training. However, this effect emerged only after participants had been prompted to actively suppress their intrusions, whereas it was not present before.…”
Section: Future Directionsmentioning
confidence: 99%
“…This issue is especially relevant given that a beneficial impact of anodal tDCS on the executive conflict network of attention has been found in a study relying on smaller electrode's sizes (i.e., 16cm2;Miler et al, 2017 Silva, 1985;Heeren et al, 2018). And, interestingly, they both have been repeatedly associated with features of the executive conflict network of attention (e.g., Bomyea, & Amir, 2011;Reinholdt-Dunne et al, 2009;Taylor et al, 2016;Verwoerd et al, 2008;Woud et al, 2019). As such, one cannot rule out the hypothesis that the mechanisms at play here are neither trait anxiety nor depression per se but rather the transdiagnostic processes that are shared between features of depression and trait anxiety.…”
Section: Discussionmentioning
confidence: 98%
“…As anxiety and depressive symptoms often covary (e.g., Brown et al, 2001;Kessler et al, 2005), our study also invites future tDCS AND ATTENTIONAL NETWORKS 18 research among patients with comorbid depression and anxiety disorders. And, lastly, given that impairments in the executive control of attention are assumed to play a role in the maintenance of a wide range of neuropsychiatric disorders (e.g., Araneda et al, 2015;Heeren et al, 2014;Maurage et al, 2014;Rochat et al, 2019;Woud et al 2019), future research may also benefit from transcending current disorder-oriented nomenclature (e.g., Hayes & Hofmann, 2018;Mansell et al, 2009;Nolen-Hoeksema & Watkins, 2011) and restrict their recruitment to patients with impairments in the executive conflict network of attention, regardless of the psychiatric diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Insbesondere Schwierigkeiten in der Kontrolle der sogenannten proaktiven Interferenz (proactive interference), wobei es zu einer Störung von Lernprozessen durch frĂŒher Gelerntes kommt, sind hierbei mit höherer Symptombelastung im Bereich Wiedererleben assoziiert [36]. So berichten Studien an gesunden Probanden, denen ein Traumafilm prĂ€sentiert wurde, dass eine bessere Kontrolle ĂŒber proaktive Interferenz zu einer geringeren Anzahl an Intrusionen nach dem Film fĂŒhrt [37][38][39], siehe aber auch [40]. Eine erste randomisierte kontrollierte Studie an Patienten mit PTBS konnte zeigen, dass ein computergestĂŒtztes Training, das auf die Kontrolle dieser proaktiven Interferenz abzielt, (1) zu einer Verbesserung der ArbeitsgedĂ€chtniskapazitĂ€t, und (2) zu einer spezifischen Reduktion intrusiver Symptome bei Patienten mit PTBS im Vergleich mit einer aktiven Kontrollaufgabe fĂŒhrt (nicht aber zu einer Reduktion anderer Symptomcluster der PTBS; [41]).…”
Section: Training Zur Verbesserung Der Interferenzkontrolle (Interferunclassified